Polymer compositions suitable for film manufacturing
By using metallocene-catalyzed heterophase polypropylene and a specific β-nucleating agent, a new polymer composition is formed, which solves the problem of difficulty in achieving excellent mechanical properties and sealing properties simultaneously in the prior art, and a combination of high impact strength and excellent sealing properties is achieved.
Patent Information
- Application Number
- CN202380060319.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-24
- Filing Date
- 2023-08-17
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing polymer compositions have difficulty achieving excellent mechanical properties and sealing properties simultaneously, especially with challenges in high impact strength and improved sealing starting temperature and thermal viscosity.
Metallocene-catalyzed heterophase polypropylene is used as the main component to combine a specific beta-nucleating agent to form a new polymer composition. The composition comprises 80-95% by weight of crystalline matrix and 5-20% by weight of amorphous propylene ethylene elastomer and the number of control region defects is measured by 13C NMR.
High impact strength and excellent sealing properties are achieved, including improved sealing starting temperature and thermal viscosity while maintaining good mechanical properties.
Smart Images

Figure BDA0005274466380000051 
Figure BDA0005274466380000141 
Figure BDA0005274466380000142
Abstract
Description
Technical Field
[0001] The present invention relates to a polymer composition suitable for the manufacture of films, comprising a specific metallocene-catalyzed heterophasic polypropylene and a specific β-nucleating agent. In addition, the present invention relates to a film made from the composition of the present invention and the use thereof. Background Art
[0002] Plastic packaging is widely used in daily life due to its good cost performance. Especially polyolefins are easy and economical to produce and have good performance, so they can be found everywhere in life. Due to different needs, multilayer products with different types of materials are used today, which on the one hand meets the needs, but the disadvantage is that these products are difficult to recycle. From the perspective of recycling, a single material solution would be preferred. At the same time, the performance of the material should not be reduced. It is still challenging to provide a polyolefin-based polymer composition with excellent mechanical properties (such as high toughness, which is usually provided by the core layer of the multilayer film) and excellent sealing properties (usually provided by the outer layer of the multilayer film).
[0003] Polymer compositions suitable for producing films are known in the art.
[0004] EP1344793A1 relates to polyolefin compositions having high impact strength and high gloss, and processes for their preparation and their use, comprising A) a heterophasic propylene copolymer containing a) 50 to 95 wt.-% of a matrix phase comprising a propylene homopolymer or a propylene copolymer having up to 5 mol-% ethylene and / or at least one C4-C8 α-olefin, and b) 5 to 50 wt.-% of a dispersed phase comprising an ethylene rubber copolymer having 20 to 80 mol-% ethylene and 80 to 20 mol-% of at least one C3-C8 α-olefin, and the intrinsic viscosity of the XCS fraction of the heterophasic copolymer being ≤ 2 dl / g, and B) a β-nucleating agent.
[0005] EP 2 055 739 A1 relates to a heterophasic propylene copolymer (HECO) wherein the heterophasic propylene copolymer (HECO) is beta-nucleated and the elastomeric phase has an intrinsic viscosity equal to or below 4.0 dl / g measured in tetralin at 135 °C.
[0006] US5310584A relates to a thermoformable sheet, a process for making the sheet, and an article thermoformed from the sheet, wherein the sheet comprises a propylene resin polymer and an effective amount of a beta spherulite nucleating agent.
[0007] US 2002 / 137851 A1 relates to polypropylene films and a method for producing these films using beta-crystalline polypropylene with high melt strength.
[0008] EP1803772A1 relates to a blown film made of a composition comprising a) a propylene heterophasic copolymer (A) having a matrix propylene polymer and an ethylene-propylene-rubber, characterised in that the film is uniaxially oriented in the machine direction with a stretch ratio of 1:1.1 to 1:10, a process for producing such a film, the use of the composition in the production of such a film, and an article comprising such a film. Summary of the invention
[0009] Based on this, an object of the present invention is to provide a polymer composition for the manufacture of films, which not only has excellent mechanical properties, in particular high impact strength, but also allows the production of films with excellent sealing properties (such as improved sealing initiation temperature and hot tack force) as well as excellent mechanical properties.
[0010] This object has been solved by a polymer composition according to claim 1 comprising the following components: a) 99.0 to 99.9999 wt.-%, based on the total weight of the polymer composition, of a metallocene-catalyzed heterophasic polypropylene comprising: i) 80 to 95 wt.-%, based on the total weight of the metallocene-catalyzed heterophasic polypropylene, of a crystalline matrix, which is a propylene homopolymer or a propylene copolymer containing 0.0 to 5.0 wt.-% of comonomers; and ii) 5 to 20 wt.-%, based on the total weight of the metallocene-catalyzed heterophasic polypropylene, of an amorphous propylene ethylene elastomer, which optionally comprises C4-C 12 α-olefin as other comonomer, the amorphous propylene ethylene elastomer is dispersed in the crystalline matrix i), wherein: the crystalline matrix i) has an MFR2 (230°C, 2.16 kg, ISO 1133) in the range of 1.0 to 10.0 g / 10min and a melting point T in the range of 130 to 160°C m (determined by DSC as described in the description); and the amorphous phase ii) has a C2 content of the XCS fraction in the range of 10 to 50 wt.-%, based on the total weight of the XCS fraction, and an IV of the XCS fraction in the range of 1.2 to 5.0 dl / g (DIN ISO 1628 / 1); and i) and ii) add up to 100 wt.-%, and b) 0.0001 to 1.0 wt.-% of a β-nucleating agent, based on the total weight of the polymer composition; wherein components a) and b) add up to 100 wt.-%.
[0011] Advantageous embodiments of the polymer composition according to the invention are specified in dependent claims 2 to 9. Furthermore, claims 10 to 14 relate to films comprising the polymer composition. The invention further relates according to claim 15 to the use of the article according to the invention as packaging material. DETAILED DESCRIPTION
[0012] definition
[0013] Indications of Quantity
[0014] The polymer composition according to the invention must contain components a) and b) and optionally additive c). It is required here that components a) and b) and additive c) (if present) add up to 100% by weight. The indicated fixed ranges for the amounts of the individual components a) and b) and optional additive c) are to be understood as meaning that any amount of each individual component can be selected within the specified range as long as the strict requirement that all components a), b) and optional additive c) add up to 100% by weight is met.
[0015] In the present invention, metallocene-catalyzed heterophasic polypropylene is defined as a heterophasic polypropylene prepared in the presence of a metallocene catalyst. The catalyst particularly affects the microstructure of the polymer. Therefore, polypropylene prepared using metallocene catalysts has a different microstructure than polypropylene prepared using Ziegler-Natta (ZN) catalysts. The most significant difference is the presence of regional defects in metallocene-prepared polypropylene, which is not the case with Ziegler-Natta (ZN) catalyst-prepared polypropylene.
[0016] Regional defects
[0017] The regional defects of propylene polymers can be of three types, namely 2,1-erythro (2,le), 2,1-threo (2,It) and 3,1 defects. A detailed description of the structure and formation mechanism of regional defects in polypropylene can be found in Chemical Review 2000, 100 (4), pages 1316-1327. Using the method described in more detail below 13 C NMR measures these defects. The term "2,1 regio defect" as used in the present invention is defined as the sum of 2,1-erythro regio defects and 2,1-threo regio defects. The propylene random copolymer or polypropylene homopolymer having the desired number of regio defects in the propylene composition of the present invention is typically and preferably prepared in the presence of a single site catalyst.
[0018] Homopolymers in the context of the present invention may comprise up to 3.0 mol-%, preferably up to 2.0 mol-%, of comonomers, based on the total weight of the homopolymer, but may also be free of comonomers.
[0019] The β-type or β-modification in the subject matter of the present invention is a specific crystalline modification of isotactic polypropylene formed during the crystallization of PP. It only exists under special conditions, such as the use of a special nucleating agent - a β nucleating agent, or a slow cooling rate, such as less than 1°C per minute.
[0020] Where the term "comprising" is used in the present description and claims, it does not exclude other unspecified elements of major or minor functional importance. For the purposes of the present invention, the term "consisting of" is considered a preferred embodiment of the term "comprising..." If a group is defined hereinafter as comprising at least a certain number of embodiments, this is also to be understood as disclosing a group that preferably consists of only these embodiments.
[0021] Whenever the terms "including" or "having" are used, these terms are meant to be equivalent to "comprising" as defined above.
[0022] Where an indefinite or definite article is used when referring to a singular noun, for example "a", "an" or "the", this includes a plural of that noun unless something else is specifically stated.
[0023] Polymer composition
[0024] The polymer composition according to the present invention comprises 99.0 to 99.9999 wt.-%, based on the total weight of the polymer composition, of a metallocene-catalyzed heterophasic polypropylene a).
[0025] The component a) comprises i) 80 to 95 wt.-%, based on the total weight of the metallocene-catalyzed heterophasic polypropylene, of a crystalline matrix which is a propylene homopolymer or a propylene copolymer containing 0.0 to 5.0 wt.-% of comonomers; and ii) 5 to 20 wt.-%, based on the total weight of the metallocene-catalyzed heterophasic polypropylene, of an amorphous propylene ethylene elastomer which optionally contains C4-C12 α-olefins as other comonomers, dispersed in the crystalline matrix i), wherein the crystalline matrix i) has an MFR2 (230° C., 2.16 kg, ISO 1133) in the range of 1.0 to 10.0 g / 10 min and a melting point T in the range of 130 to 160° C. m (determined by DSC as described in the description); and the amorphous phase ii) has a C2 content of the XCS fraction in the range of 10 to 50 wt.-%, based on the total weight of the XCS fraction, and an IV (DIN ISO 1628 / 1) of the XCS fraction in the range of 1.2 to 5.0 dl / g; and i) and ii) add up to 100 wt.-%.
[0026] Preferred embodiments of the metallocene-catalyzed heterophasic polypropylene a) are described below.
[0027] According to a preferred embodiment of the present invention, component a) has 13 The number of 2,1 regio defects and 3,1 regio defects is in the range of 0.01 to 1.2 mol-%, preferably in the range of 0.1 to 1.0 mol-%, more preferably in the range of 0.3 to 0.9 mol-%, as measured by C NMR.
[0028] According to a preferred embodiment, the content of crystalline matrix i) is in the range of 85 to 94 wt.-%, preferably in the range of 88 to 93 wt.-%, more preferably in the range of 90 to 92 wt.-%, based on the total weight of component a), and the content of amorphous polypropylene ethylene elastomer ii) is in the range of 6 to 15 wt.-%, preferably 7 to 12 wt.-%, more preferably 8 to 10 wt.-%, based on the total weight of component a). The content of crystalline matrix i) and amorphous polypropylene ethylene elastomer ii) can be determined by the xylene cold soluble (XCS) fraction determined according to ISO 16152.
[0029] A further preferred embodiment provides that the crystalline matrix i) is a homopolymer.
[0030] According to a further preferred embodiment of the present invention, polymer a) has a xylene cold soluble (XCS) fraction determined to ISO 16152 of 6 to 20 wt.-%, preferably 8 to 13 wt.-%, based on the weight of the metallocene-catalyzed heterophasic polypropylene a).
[0031] According to another preferred embodiment of the present invention, the metallocene-catalyzed heterophasic polypropylene a) has an MFR2 (230° C., 2.16 kg, ISO 1133) in the range of 1 to 10 g / 10 min, preferably 1.5 to 5 g / 10 min, more preferably 1.5 to 3.0 g / 10 min.
[0032] A further preferred embodiment of the present invention provides that the metallocene-catalyzed heterophasic polypropylene a) has a C2 content in the range of 0.5 to 4 wt.-%, preferably 1.3 to 2.0 wt.-%, based on the total weight of component a).
[0033] According to a further preferred embodiment of the present invention, it is provided that the metallocene-catalyzed heterophasic polypropylene a) has a C2 content of the xylene cold soluble (XCS) fraction in the range of 10 to 40 wt.-%, preferably 20 to 25 wt.-%, based on the total weight of the xylene cold soluble (XCS) fraction.
[0034] In another preferred embodiment according to the present invention the metallocene-catalyzed heterophasic polypropylene a) has an intrinsic viscosity of the xylene cold soluble (XCS) fraction in the range of 1.0 to 5.0 dl / g and preferably in the range of 2.0 to 2.7 dl / g.
[0035] Further according to the present invention, the metallocene-catalyzed heterophasic polypropylene a) is present in the polymer composition predominantly in its [beta]-nucleated form, preferably in an amount of 50 to 99 wt%, more preferably 75 to 88 wt% (determined by WAXS).
[0036] Another preferred embodiment of the present invention provides that the heterophasic polymer a) is produced in the presence of a metallocene catalyst, preferably a metallocene catalyst comprising a complex as described in any of WO 2013 / 007650 A1, WO 2015 / 158790 A2 and WO 2018 / 122134 A1. In another preferred embodiment of the present invention, a cocatalyst system comprising a boron-containing cocatalyst (e.g., a borate cocatalyst) and an aluminoxane cocatalyst is used.
[0037] According to a preferred embodiment of the present invention, the metallocene-catalyzed heterophasic polypropylene a) is produced in the presence of a catalyst system comprising:
[0038] (i) a metallocene complex of the general formula (I),
[0039]
[0040] wherein each X is independently a σ-donor ligand,
[0041] L is a divalent bridge selected from -R'2C-, -R'2C-CR'2-, -R'2Si-, -R'2Si-SiR'2-, -R'2Ge-, wherein each R' is independently a hydrogen atom or a C1-C2-atom optionally containing one or more heteroatoms or fluorine atoms from Groups 14 to 16 of the Periodic Table of Elements. 20 A hydrocarbon group, or optionally two R' groups together may form a ring,
[0042] Each R 1 are independently the same or may be different and are hydrogen, linear or branched C1-C6 alkyl, C 7-20 Aralkyl, C 7-20 Alkyl or C 6-20 Aryl or OY group, where Y is C 1-10 A hydrocarbon group, and optionally two adjacent R 1 The groups may be part of a ring including the phenyl carbon to which they are bonded,
[0043] Each R2 are independently the same or may be different and are CH2-R 8 Group, where R 8 H or a straight or branched C 1-6 Alkyl, C 3-8 Cycloalkyl, C 6-10 Aryl,
[0044] R 3 is a straight or branched C1-C6 alkyl group, C 7-20 Aralkyl, C 7-20 Alkyl or C6-C 20 Aryl,
[0045] R 4 C(R 9 )3 groups, wherein R 9 is a linear or branched C1-C6 alkyl group,
[0046] R 5 is hydrogen or optionally contains one or more heteroatoms from Groups 14 to 16 of the Periodic Table of the Elements. 20 Hydrocarbon;
[0047] R 6 is hydrogen or optionally contains one or more heteroatoms from Groups 14 to 16 of the Periodic Table of the Elements. 20 Hydrocarbyl; or
[0048] R 5 and R 6 can together form a 5-membered saturated carbocyclic ring, which may be optionally substituted by n groups R 10 substitution, n is 0 to 4;
[0049] Each R 10 Same or different, can be C1-C 20 A hydrocarbon group, or a C1-C ... 20 Hydrocarbon;
[0050] R 7 is H or a linear or branched C1-C6 alkyl group or optionally substituted by one to three R 11 a radical-substituted aryl or heteroaryl group having 6 to 20 carbon atoms,
[0051] Each R 11 are independently the same or may be different and are hydrogen, linear or branched C1-C6 alkyl, C 7-20 Aralkyl, C 7-20 Alkyl or C 6-20 Aryl or OY group, where Y is C 1-10 Hydrocarbon,
[0052] (ii) a cocatalyst system comprising a boron-containing cocatalyst and / or an aluminoxane cocatalyst, and
[0053] (iii) Silica support.
[0054] According to another preferred embodiment of the present invention, the metallocene complex is selected from the group consisting of racemic-dimethylsilanediylbis[2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, racemic-trans-dimethylsilanediyl[2-methyl-4-(4'-tert-butylphenyl)-inden-1-yl][2-methyl-4-(4'-tert-butylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, racemic-trans-dimethylsilanediylbis ... alkanediyl[2-methyl-4-(4'-tert-butylphenyl)-inden-1-yl][2-methyl-4-phenyl-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, racemic-trans-dimethylsilanediyl[2-methyl-4-(3',5'-tert-butylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, Racemic-trans-dimethylsilanediyl[2-methyl-4,8-bis-(4'-tert-butylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, racemic-trans-dimethylsilanediyl[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl acen)-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, and racemic-trans-dimethylsilanediyl[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl][2-methyl-4-(3',5'-5 di-tert-butylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride.
[0055] The polymer composition according to the invention further comprises 0.0001 to 1.0 wt. %, based on the total weight of the polymer composition, of a β-nucleating agent b).
[0056] Preferred embodiments of the β-nucleating agents b) are described below.
[0057] According to a preferred embodiment of the present invention, the β-nucleating agent b) is selected from N,N'-dicyclohexyl-2,6-naphthalene dicarboxamide, quinol[2,3-b]acridine-6,7,13,14(5H,12H)-tetraketone, an organic metal salt type β-nucleating agent and a mixture thereof, preferably an organic metal salt type β-nucleating agent, and more preferably the polymer composition does not contain an α-nucleating agent.
[0058] Suitable organometallic salt type β-nucleating agents are commercially available, for example, from GCH (CN) under the trade name NAB-82. N, N'-dicyclohexyl-2,6-naphthalenedicarbamide is commercially available, for example, from New Japan Chemical under the trade name NJ Star Nu-100. Quinolinyl [2,3-b] acridine-6,7,13,14 (5H,12H) -tetraone is commercially available from BASF.
[0059] Another preferred embodiment of the present invention provides that the polymer composition has an MFR2 (230° C., 2.16 kg, ISO 1133) in the range of 1.0 to 10.0 g / 10 min, preferably in the range of 1.5 to 5.0 g / 10 min, more preferably in the range of 2.0 to 4.0 g / 10 min.
[0060] In another preferred embodiment of the present invention, the polymer composition has a melting point T in the range of 140 to 160° C., preferably 155 to 160° C. m1 and a melting point T in the range of 120 to 160° C., preferably in the range of 140 to 150° C. m2 (all measured by DSC as described in the specification), where T m1 >T m2 And the crystallization temperature T c >114°C, preferably in the range of >114 to 125°C.
[0061] According to another preferred embodiment of the present invention, a 50 μm blown film of the polymer composition (produced as described in the specification) has a K of >0.60, preferably >0.70, even more preferably >0.80, still more preferably from 0.80 to 0.99, most preferably from 0.85 to 0.98. β (determined by wide angle X-ray scattering as described in the specification).
[0062] According to another preferred embodiment of the present invention, the polymer composition has a strength of greater than 45 kJ / m 2 , preferably 50.0 to 90.0 kJ / m 2 In the range of 60.0 to 80.0 kJ / m 2 Notched impact strength NIS in the range (measured according to ISO179 / 1eA at +23°C).
[0063] According to another preferred embodiment of the invention, it is provided that the polymer composition has a flexural modulus (determined according to ISO 178) of more than 800 MPa, preferably in the range of 900 to 1500 MPa, more preferably in the range of 1000 to 1200 MPa.
[0064] According to another preferred embodiment of the present invention, the polymer composition has a xylene cold soluble (XCS) fraction determined according to ISO 16152 of 6 to 20 wt.-%, preferably 8 to 13 wt.-%, based on the weight of the metallocene-catalyzed heterophasic polypropylene a).
[0065] According to another preferred embodiment of the present invention, the polymer composition comprises 99.5 to 99.95 wt%, preferably 99.6 to 99.8 wt%, based on the total weight of the polymer composition, of a metallocene-catalyzed heterophasic polypropylene a); and 0.05 to 0.2 wt%, preferably 0.075 to 0.125 wt%, based on the total weight of the polymer composition, of a nucleating agent b); wherein the polymer composition further comprises an additive c) different from b), and components a), b) and c) add up to 100 wt%.
[0066] In another preferred embodiment of the invention, the additive c) is selected from antioxidants, hydrotalcites (preferably synthetic hydrotalcites), slip agents, antiblocking agents, UV stabilizers and mixtures thereof. It is further preferred that no additives acting as alpha-nucleating agents are present in the polymer composition according to the invention.
[0067] film
[0068] Another aspect of the present invention relates to a film, preferably a blown film, comprising at least one layer comprising at least 90% by weight, preferably at least 95% by weight, more preferably at least 99% by weight of the polymer composition according to the present invention. The film may also consist of the polymer composition.
[0069] According to a preferred embodiment of the present invention, the film comprises a sealing layer, which comprises the polymer composition according to the present invention.
[0070] In another embodiment of the present invention, the film has a dart drop strength (ISO 7765-1) of >150 g, preferably in the range of 300 to 1000 g, more preferably in the range of 350 to 600 g.
[0071] A further preferred embodiment of the invention provides that the film has a sealing initiation temperature in the range from 120 to 135° C., preferably in the range from 129 to 131° C. (determination as described in the description).
[0072] According to another preferred embodiment of the present invention, the film has a hot tack in the range of 5.1 to 7.0 N, preferably in the range of 5.3 to 6.0 N (measured as described in the description).
[0073] In another embodiment of the present invention, the film has a hot stick temperature in the range of 125 to 136°C, preferably in the range of 128 to 133°C.
[0074] Another preferred embodiment of the invention provides that the film has a tensile modulus (in the machine direction and in the transverse direction) above 1000 MPa, preferably in the range of 1050 to 1500 MPa, more preferably in the range of 1080 to 1250 MPa.
[0075] According to another preferred embodiment of the present invention, the film has a crystallinity index X in the range of 55 to 80%, preferably in the range of 60 to 66%. c .
[0076] In another embodiment of the present invention, the crystalline phase K of the film β The amount of the β-type polypropylene is in the range of 0.6 to 0.99, preferably in the range of 0.95 to 0.98.
[0077] The film of the present invention preferably has a thickness in the range of 20 to 200 μm, preferably in the range of 30 to 100 μm, more preferably in the range of 40 to 60 μm.
[0078] Generally, the film of the present invention can be produced by a blown film process or a cast film process, preferably by a blown film process.
[0079] To make such films, for example, at least three polymer melts are simultaneously extruded (i.e., coextruded) through a multichannel tubular, annular or circular die to form a tube that is blown, inflated and / or cooled with air (or a combination of gases) to form a film. The manufacture of blown film is a well-known process.
[0080] Blown (co)extrusion may be carried out at a temperature in the range of 150 to 230°C, more preferably 160 to 225°C, and cooled by blowing (typically air) at a temperature of 10 to 40°C, more preferably 12 to 16°C, to provide a frost line height of 0.5 to 4 times, more preferably 1 to 2 times, the die diameter.
[0081] The blow up ratio (BUR) should generally be in the range of 1.5 to 3.5, preferably 2.0 to 3.0, more preferably 2.1 to 2.8.
[0082] All preferred aspects and embodiments described above for the polymer composition also apply to the film according to the invention.
[0083] use
[0084] A further aspect of the invention relates to the use of the film according to any of the preceding claims as packaging material, preferably for food and / or pharmaceutical products.
[0085] The invention will now be described with reference to the following non-limiting examples.
[0086] Experimental Section
[0087] A. Measurement Method
[0088] Unless otherwise defined, the following definitions of terms and determination methods apply to the above general description of the invention as well as the following examples.
[0089] Melt flow rate
[0090] The melt flow rate (MFR) is determined according to ISO 1133 (Determination of melt mass-flow rate (MFR) and melt volume-flow rate (MVR) of thermoplastics - Part 1: Standard method) and is expressed in g / 10 min. The MFR is an indication of the flowability and therefore the processability of the polymer. The higher the melt flow rate, the lower the viscosity of the polymer. The MFR of polypropylene is determined at a temperature of 230°C and a load of 2.16 kg (MFR2).
[0091] DSC analysis, melting temperature (T m ) and crystallization temperature (T c ) and β content
[0092] Data measurements were performed on 5 mg to 7 mg samples using a TA Instruments Q2000 Differential Scanning Calorimeter (DSC). The DSC was run according to ISO 11357 / Part 3 / Method C2 in a heating / cooling / heating cycle at a scan rate of 10°C / min over a temperature range of -30 to +225°C.
[0093] Crystallization temperature (T c ) and crystallization enthalpy (H c ) is determined by the cooling step, while the melting temperature (T m ) and melting enthalpy (H m ) is determined by the second heating step. The beta content of the material can be determined as follows:
[0094] Among them, H m2 is the melting enthalpy of the β-form, H m1 is the melting enthalpy of the α-form, both of which are determined by the second heating step. As mentioned above, the melting point T m1 and T m2is determined in the second heating step, where T m1 Only applicable to α-type polymers, while T m2 Applicable only to β-type polymers.
[0095] Dart Drop Intensity (DDI): Impact resistance measured by the free-falling dart method
[0096] The DDI of the films produced as shown below was measured according to ISO7765-1:1988 / Method A. This test method covers the determination of the energy of a film to be broken by a dart falling freely from a specified height under specified conditions, which will cause 50% of the tested specimens to break (Step Method A). During the test, uniform increments of the thrown mass are used, and after each sample is tested, the thrown weight is reduced or increased in uniform increments depending on the observation of the sample (broken or unbroken).
[0097] Standard conditions:
[0098] Adjustment time: >96 hours
[0099] Test temperature: 23℃
[0100] Dart head material: phenolic resin
[0101] Dart diameter: 38mm
[0102] Drop height: 660mm
[0103] result:
[0104] Impact damage weight - 50% [g].
[0105] Notched Impact Strength (NIS)
[0106] According to ISO 179 1eA, at -20°C, 0°C and +23°C, using 80×10×4 mm prepared according to ISO 19069-2 3 The injection molded bar test specimens were tested to determine the Charpy notched impact strength (NIS).
[0107] Flexural modulus
[0108] According to ISO178, use 80×10×4mm injection molded according to ISO19069-2 3 The bars were tested and the flexural modulus was determined by three-point bending at 23°C.
[0109] Intrinsic viscosity
[0110] The intrinsic viscosity (iV) is measured in decalin at 135°C according to DIN ISO 1628 / 1 (October 1999).
[0111] Xylene cold soluble fraction (XCS)
[0112] The "xylene cold soluble" (XCS) fraction and the "xylene cold insoluble" (XCI) fraction were determined separately by the standard gravimetric method according to ISO 16152.
[0113] Sealing start temperature (SIT); sealing end temperature (SET), sealing range
[0114] This method determines the sealing temperature range (sealing range) of polypropylene films (especially blown films or cast films) produced as follows. The sealing temperature range is the temperature range within which the film can be sealed according to the conditions given below.
[0115] The lower limit (seal initiation temperature (SIT)) is the sealing temperature at which a seal strength of 5 N is obtained. The upper limit (seal termination temperature (SET)) is reached when the film sticks to the sealing device.
[0116] The measurements were carried out according to a slightly modified ASTM F1921-12, where the test parameters sealing pressure, cooling time and test speed were modified. The force / temperature curve was measured until the film failed thermally.
[0117] The sealing range is determined on a J&B Universal Sealer Model 4000 with a blown film thickness of 50 μm according to the following further parameters:
[0118] Adjustment time: >96 hours
[0119] Sample width: 25mm
[0120] Sealing pressure: 0.67N / mm 2 (PP)
[0121] Sealing time: 1s
[0122] Delay time: 30s
[0123] Sealing jaw size: 50×5mm
[0124] Sealing jaw shape: flat
[0125] Sealing jaw coating: Niptef
[0126] Sealing temperature: ambient temperature -240℃
[0127] Sealing temperature interval: 5°C
[0128] Starting temperature: 50℃
[0129] Clamping separation rate: 42mm / s.
[0130] Hot Tack Temperature (HTT) and Hot Tack Force (HTF)
[0131] HTT (lowest temperature to obtain maximum hot tack) and HTF (maximum hot tack) were measured with a 50 μm thick film according to ASTM F 1921 Method B using the following settings:
[0132] Q-Name Instrument: Hot Tack-Seal Tester
[0133] Model: J&B Model 4000MB
[0134] Sealing strip length: 50[mm]
[0135] Sealing strip width: 5[mm]
[0136] Sealing strip shape: flat
[0137] Sealing pressure: 0.15N / mm 2
[0138] Sealing time: 1s
[0139] Sealing strip coating:
[0140] Sealing strip coating roughness: 1[μm]
[0141] Film sample width: 25mm
[0142] Cooling time: 0.2s
[0143] Peeling speed: 200mm / s
[0144] Starting temperature: 50℃
[0145] Termination temperature: burn-through and / or shrinkage
[0146] Increment: 5°C.
[0147] All film test samples were prepared in a standard atmosphere, conditioned and tested at 23°C (±2°C) and 50% (±10%) relative humidity. The minimum conditioning time of the test samples in the standard atmosphere before starting the test was at least 40 hours. The minimum storage time between the extrusion of the film samples and the start of the test was at least 88 hours. The hot tack measurement determines the strength of the heat seal formed in the film immediately after the seal is completed and before it cools to ambient temperature.
[0148] The HTF is measured as a function of temperature over the temperature range, using the temperature increments mentioned above. The number of test specimens at each temperature is at least 3 specimens. The HTF is evaluated as the maximum force (maximum peak value) with failure mode "peeling".
[0149] The C2 content of the calibration standards was based on 13 C NMR spectroscopy
[0150] Adopt 1 H and 13 Quantitative NMR spectrometers were recorded in solution on a Bruker Avance III 400 NMR spectrometer operating at 400.15 and 100.62 MHz, respectively. 13 C{ 1 H} NMR spectra. All spectra were obtained using 13 C optimized 10mm extended temperature probe was recorded at 125°C, using nitrogen for all pneumatic devices. About 200mg of material and chromium (III) acetylacetonate (Cr(acac)3) were dissolved in 3ml 1,2-tetrachloroethane-d2 (TCE-d2) to obtain a 65mM solution of the relaxation agent in the solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475). To ensure a homogeneous solution, the NMR tube was further heated in a rotary oven for at least 1 hour after the initial sample preparation in the heating block. After insertion of the magnet, the tube was rotated at 10Hz. This setting was chosen mainly for high resolution and quantification required for accurate quantification of ethylene content. Standard single pulse excitation without NOE was used, with an optimized tip angle, 1 second recycle delay, and a two-stage WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D. Winniford, B., J. Mag. Reson. 187 (2007) 225, Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transients were acquired for each spectrum. For quantitative 13 C{ 1 The H} NMR spectra were processed, integrated, and the relevant quantitative properties were determined from the integrals. All chemical shifts were indirectly referenced to the central methylene of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. This approach allows for comparable references even if this structural unit is not present.
[0151] Characteristic signals corresponding to ethylene incorporation were observed (Cheng, HN, Macromolecules 17 (1984), 1950), and the comonomer fraction was calculated as the fraction of ethylene in the polymer relative to all monomers in the polymer:
[0152] fE=(E / (P+E))
[0153] Using the method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157), 13 C{ 1 The comonomer fraction is quantified by integrating multiple signals over the entire spectral region in the {H} spectrum. This method was chosen for its stability and ability to account for the presence of regio defects when required. Slight adjustments to the integration region are made to improve applicability over the entire range of comonomer content encountered. For systems with very low ethylene content, where only isolated ethylene is observed in the PPEPP sequence, the method of Wang et al. is modified to reduce the impact of integration over sites that are no longer present. This approach reduces the overestimation of ethylene content for such systems and is achieved by reducing the number of sites used to determine the absolute ethylene content to:
[0154] E=0.5(Sββ+Sβγ+Sβδ+0.5(Sαβ+Sαγ))
[0155] Using this set of sites, the corresponding integral equation becomes:
[0156] E=0.5(I H +I G +0.5(I C +I D ))
[0157] The same symbols as in the article by Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) are used. The formula used for absolute propylene content is not modified. Calculation of comonomer mole percentage from mole fraction:
[0158] E[mol%]=100*fE.
[0159] Calculate the weight percent of comonomer from the mole fraction:
[0160] E[weight%]=100*(fE*28.06) / ((fE*28.06)+((1-fE)*42.08)).
[0161] Quantification of microstructure (comonomer content & regio defects) by NMR spectroscopy
[0162] Quantitative nuclear magnetic resonance (NMR) spectroscopy was further used to quantify the comonomer content and comonomer sequence distribution of the polymers. 1 H and 13 Quantitative analysis in solution was recorded on a Bruker Advance III 400 NMR spectrometer operating at 400.15 and 100.62 MHz, respectively. 13 C{ 1 H} NMR spectra. All spectra were obtained using 13 C optimized 10mm extended temperature probe was recorded at 125°C, using nitrogen for all pneumatic components. About 200mg of material was dissolved in 3ml 1,2-tetrachloroethane-d2 (TCE-d2) along with chromium-(III)-acetylacetone (Cr(acac)3) to obtain a 65mM solution of the relaxation agent in the solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475). To ensure a homogeneous solution, the NMR tube was heated in a rotary oven for at least 1 hour after initial sample preparation in a heating block. After insertion of the magnet, the tube was rotated at 10Hz. This setup was chosen primarily to obtain high resolution and since quantification of accurate ethylene content is quantitatively required. Standard single pulse excitation without NOE was used, using an optimized tip angle, 1 second recycle delay, and a two-stage WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D. Winniford, B., J. Mag. Reson. 187 (2007) 225; Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transients were acquired for each spectrum.
[0163] A proprietary computer program was used to quantify 13 C{ 1 H} NMR spectra are processed, integrated and relevant quantitative properties are determined from the integration. All chemical shifts are indirectly referenced to the central methylene group of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. This method allows for comparable references even if the structural unit is not present. Characteristic signals corresponding to ethylene incorporation are observed (Cheng, HN, Macromolecules 17 (1984), 1950).
[0164] Since characteristic signals corresponding to 2,1 erythro-type regio defects were observed (as described in L. Resconi, L. Cavallo, A. Fait, F. Piemontesi, Chem. Rev. 2000, 100 (4), 1253, in Cheng, HN, Macromolecules 1984, 17, 1950, and in WJ. Wang and S. Zhu, Macromolecules 2000, 33 1157), it is necessary to correct for the effects of regio defects on the measured properties. Characteristic signals corresponding to other types of regio defects were not observed.
[0165] Wide-angle X-ray scattering (WAXS)
[0166] Wide angle X-ray scattering (WAXS) measurements of the samples were performed by a Bruker D8 Discover instrument. The diffractometer was equipped with an X-ray tube with a copper target operated at 30 kV and 20 mA and a GADDS2-D detector. Point collimation (0.5 mm) was used to direct the beam onto the surface. The measurements were performed in reflection geometry and 28 angles ranging from 10° to 32.5° were measured. The data was collected for 300 seconds. The intensity versus 2θ (2-theta) curves of the amorphous polypropylene sample prepared by solvent extraction were obtained using the same measurement parameters. The amorphous halo was obtained by smoothing the curve. The amorphous halo was subtracted from the measured intensity versus 2θ (2-theta) curve to obtain the crystallization curve.
[0167] The crystallinity index X is obtained by using the following method of Challa, Hermans and Weidinger [Challa G, Hermans PH, Weidinger A, Makromol. Chem. 56, 169 (1962)]. c It can be defined using the area under the crystallization curve and the original spectrum:
[0168]
[0169] Crystalline phase K β The amount of β-type polypropylene in the mixture was calculated using the Jones method [Turner-Jones A, Aizlewood JM, Beckett DR, Makromol. Chem. 75, 134 (1974)] according to the following equation:
[0170]
[0171] Wherein, Iβ(300) is the intensity of the β(300) peak, Iα(110) is the intensity of the α(110) peak, Iα(040) is the intensity of the α(040) peak, and Iα(130) is the intensity of the α(130) peak after subtracting the amorphous halo.
[0172] The amount of γ-form of isotactic polypropylene (iPP) in the crystalline phase Kγ is calculated using the method developed by Pae [Pae KD, J. Polym. Sci., Part A, 6, 657 (1968)] as follows:
[0173]
[0174] Where Iα(130) is the intensity of the α(130) peak, and Iγ(117) is the intensity of the γ(117) peak obtained after subtracting the baseline connecting these peaks.
[0175] The quantification of the three-phase crystalline system was performed according to the procedure described in Obadal M, Cermak R, Stoklasa K, Macromol. Rapid Commun. 26, 1253 (2005).
[0176] For a three-phase crystalline system, the following equation is used to determine K α (amount of α phase), K β (amount of β phase) and K γ (Amount of γ phase):
[0177]
[0178] K α+γ =1-K β ,
[0179] K γ =G X K α+γ ,
[0180] and
[0181] K α =1-K β -K γ
[0182] Tensile modulus (TM)
[0183] Tensile modulus (MPa) was measured in the machine direction (MD) and transverse direction (TD) according to ISO 527-3 using film samples (prepared as described below, crosshead speed of 1 mm / min).
[0184] B. Materials used
[0185] AO is an antioxidant commercially available as Irganox B 215 (FF) from BASF SE (CH).
[0186] SHT is a synthetic hydrotalcite commercially available as DHT-4V from Kisuma Chemicals (NL).
[0187] NU is an organometallic salt type β-nucleating agent, commercially available as NAB-82 from GCH (CN).
[0188] HECO is a SSC-based C2C3-heterophasic copolymer prepared as follows.
[0189] Catalyst preparation (CAT)
[0190] Catalyst synthesis
[0191] The metallocene (MC) used was trans-dimethylsilanediyl[2-methyl-4,8-di(3,5-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl][2-methyl-4-(3,5-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride as ICS3 disclosed in EP19177308.4.
[0192] Preparation of MAO-silica carrier
[0193] A steel reactor equipped with a mechanical stirrer and a filter screen was flushed with nitrogen and the reactor temperature was set to 20°C. Then, silicon dioxide (5.0 kg) of the grade DM-L-303 of AGC Si-Tech Company pre-calcined at 600°C was added from the feed bucket, and then carefully pressurized and decompressed with nitrogen using a manual valve. Toluene (22 kg) was then added. The mixture was stirred for 15 minutes, and then a solution (9.0 kg) of 30% by weight MAO in toluene from Lanxess was added through the feed line at the top of the reactor within 70 minutes. The reaction mixture was then heated to 90°C and stirred for another two hours at this temperature. The slurry was then allowed to settle and the mother liquor was filtered off. At 90°C, the catalyst was washed twice with toluene (22 kg), then settled and filtered. The reactor was cooled to 60°C and the solid was washed with heptane (22.2 kg). Finally, the SiO2 treated with MAO was dried at 60°C under a nitrogen stream for 2 hours, and then stirred under vacuum (-0.5 bar) for 5 hours. The MAO treated support was collected as a free flowing white powder which was found to contain 12.2 wt% Al.
[0194] Catalyst preparation
[0195] At 20°C, 30 wt% MAO (0.7 kg) in toluene was added to a steel nitrogen blank reactor via a burette. Toluene (5.4 kg) was then added under stirring. The above MC (93 g) was added from a metal cylinder and then rinsed with 1 kg toluene. The mixture was stirred for 60 minutes at 20°C. Trityl tetrakis(pentafluorophenyl)borate (91 g) was then added from a metal cylinder and then rinsed with 1 kg toluene. The mixture was stirred for 1 hour at room temperature. The resulting solution was added to the MAO-silica support stirred cake prepared as described above over a period of more than 1 hour. The cake was left to stand for 12 hours, then dried for 2 hours under a nitrogen stream at 60°C and dried for another 5 hours under vacuum (-0.5 bar) under stirring. The dried catalyst was sampled in the form of a pink free-flowing powder containing 13.9 wt% Al and 0.11 wt% % Zr.
[0196] polymerization:
[0197] The polymerization reaction was carried out in a Borstar pilot plant having three reactor units (loop-GPR-GPR2) and a prepolymerization loop reactor. The specific conditions are shown in Table 1.
[0198] Table 1: Polymerization conditions.
[0199]
[0200]
[0201] Table 2 summarizes some characteristics of HECO.
[0202] Table 2: Characteristics of HECO.
[0203]
[0204]
[0205] The polymer powder was mixed with the other ingredients shown in Table 3 below under a nitrogen atmosphere. Then, the polymer powder was extruded using a ZSK18 twin-screw extruder (T m =210°C, productivity 7kg / h) were mixed and extruded into pellets under a nitrogen atmosphere.
[0206] C. Manufacturing of blown film
[0207] Blown films were produced on a Collin lab-scale blown film line with the composition shown in Table 3, with a total thickness of 50 μm (melt temperature: 210° C., BUR 1:2.5, ramp speed: 7 m / min).
[0208] D. Results
[0209] Table 3: Polymer compositions and composition and properties of blown films.
[0210]
[0211]
[0212] nm = not determined;
[0213] nd = not detected;
[0214] The total amount of 2,1 and 3,1 regio defects in HECO is 0.6 mol-%.
[0215] E. Discussion of Results
[0216] The polymer composition of the comparative example (CE1) contains the same base polymer and the same stabilizer package as the polymer composition of the inventive example (IE1), but does not contain a β-nucleating agent. As can be seen from Table 3 above, the polymer composition according to the invention contains 83.0% of the β-modification measured by DSC. Furthermore, as can be seen from said table, the stiffness (expressed by flexural modulus) of the polymer composition of the invention is only slightly inferior, while the impact strength (expressed by notched impact strength (NIS)) is greatly increased. Moreover, both IE and CE are converted into blown films, with IE having a sufficiently high amount of the β-form (measured as k by WAXS). β ), while CE has a negligible amount of β-polypropylene. Therefore, the blown film prepared from the polymer composition of the present invention not only shows improved sealing performance (indicated by lower seal initiation temperature and higher hot tack), but also shows better mechanical properties (indicated by dart impact strength with little loss of stiffness).
Claims
1. A polymer composition suitable for making a film, comprising the following components: a) 99.0 wt% to 99.9999 wt%, based on the total weight of the polymer composition, of a metallocene-catalyzed heterophasic polypropylene comprising: i) 80 to 95 wt% of a crystalline matrix, based on the total weight of the metallocene-catalyzed heterophasic polypropylene, the crystalline matrix being a propylene homopolymer or a propylene copolymer containing 0.0 to 5.0 wt% of comonomer; and ii) 5 to 20 wt% of an amorphous propylene ethylene elastomer, optionally containing C4-C12 α-olefins as other comonomers, dispersed in the crystalline matrix i), based on the total weight of the metallocene-catalyzed heterophasic polypropylene, wherein: The crystalline matrix i) has an MFR2 (230°C, 2.16 kg, ISO 1133) in the range of 1.0 to 10.0 g / 10 min and a melting point T in the range of 130 to 160°C. m (determined by DSC as described in the specification); and the amorphous phase ii) has a C2 content of the XCS fraction in the range of 10 to 50 wt.-%, based on the total weight of the XCS fraction, and an IV (DIN ISO 1628 / 1) of the XCS fraction in the range of 1.2 to 5.0 dl / g; and i) and ii) add up to 100% by weight, and b) 0.0001 wt % to 1.0 wt % of a β-nucleating agent; in Components a) and b) add up to 100% by weight.
2. The polymer composition according to claim 1, characterized in that The polymer composition has an MFR2 (230°C, 2.16 kg, ISO 1133) in the range of 1 to 10 g / 10 min, preferably in the range of 1.5 to 5 g / 10 min, more preferably in the range of 2.0 to 4.0 g / 10 min; Component a) has 13 The total amount of 2,1 regio defects and 3,1 regio defects ranged from 0.01 to 1.2 mol % as measured by C NMR.
3. The polymer composition according to claim 1 or 2, characterized in that The polymer composition has a melting point T in the range of 140 to 160° C., preferably in the range of 155 to 165° C. m1 and a melting point T in the range of 120 to 160° C., preferably in the range of 140 to 150° C. m2 (all measured by DSC as described in the specification), where T m1 >T m2 And the crystallization temperature T c >114°C (measured by DSC as described in the specification), preferably in the range of 114 to 125°C.
4. The polymer composition according to any one of the preceding claims, characterized in that A 50 μm blown film of the polymer composition (produced as described in the specification) has a K of >0.60, preferably >0.70, more preferably >0.80, still more preferably from 0.80 to 0.99, most preferably from 0.85 to 0.
98. β (determined by wide angle X-ray scattering as described in the instructions).
5. The polymer composition according to any one of the preceding claims, characterized in that The polymer composition has a strength of >45 kJ / m 2 , preferably 50.0 to 90.0 kJ / m 2 In the range of 60.0 to 80.0 kJ / m 2 Notched impact strength NIS in the range (measured according to ISO179 / 1eA at +23°C).
6. The polymer composition according to any one of the preceding claims, characterized in that The metallocene-catalyzed heterophasic polypropylene a) is produced in the presence of a catalyst system comprising: (i) Metallocene complex of general formula (I) wherein each X is independently a σ-donor ligand, L is a divalent bridge selected from -R'2C-, -R'2C-CR'2-, -R'2Si-, -R'2Si-SiR'2-, -R'2Ge-, wherein each R' is independently a hydrogen atom or a C1-C2-atom optionally containing one or more heteroatoms or fluorine atoms from Groups 14 to 16 of the Periodic Table of Elements. 20 A hydrocarbon group, or optionally two R' groups together may form a ring, Each R 1 are independently the same or may be different and are hydrogen, linear or branched C1-C6 alkyl, C 7-20 Aralkyl, C 7-20 Alkyl or C 6-20 Aryl or OY group, where Y is C 1-10 A hydrocarbon group, and optionally two adjacent R 1 The groups may be part of a ring including the phenyl carbon to which they are bonded, Each R 2 are independently the same or may be different and are CH2-R 8 Group, where R 8 H or a straight or branched C 1-6 Alkyl, C 3-8 Cycloalkyl, C 6-10 Aryl, R 3 is a straight or branched C1-C6 alkyl group, C 7-20 Aralkyl, C 7-20 Alkyl or C6-C 20 Aryl, R 4 C(R 9 )3 groups, wherein R 9 is a linear or branched C1-C6 alkyl group, R 5 is hydrogen or optionally contains one or more heteroatoms from Groups 14 to 16 of the Periodic Table of the Elements. 20 Hydrocarbon; R 6 is hydrogen or optionally contains one or more heteroatoms from Groups 14 to 16 of the Periodic Table of the Elements. 20 Hydrocarbyl; or R 5 and R 6 can form a 5-membered saturated carbocyclic ring, which may be optionally substituted by n R 10 Group substitution, n is 0 to 4; Each R 10 Same or different, can be C1-C 20 A hydrocarbon group, or a C1-C ... 20 Hydrocarbon; R 7 is H or a linear or branched C1-C6 alkyl group or optionally substituted by one to three R 11 a radical-substituted aryl or heteroaryl group having 6 to 20 carbon atoms, Each R 11 are independently the same or may be different and are hydrogen, linear or branched C1-C6 alkyl, C 7-20 Aralkyl, C 7-20 Alkyl or C 6-20 Aryl or OY group, where Y is C 1-10 Hydrocarbon, (ii) a cocatalyst system comprising a boron-containing cocatalyst and / or an aluminoxane cocatalyst, and (iii) Silica support.
7. The polymer composition according to claim 6, characterized in that The metallocene complex is selected from the group consisting of racemic-dimethylsilanediylbis[2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, racemic-trans-dimethylsilanediyl[2-methyl-4-(4'-tert-butylphenyl)-inden-1-yl][2-methyl-4-(4'-tert-butylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, racemic-trans-dimethylsilanediylbis ... Dimethyl[2-methyl-4-(4'-tert-butylphenyl)-inden-1-yl][2-methyl-4-phenyl-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, racemic-trans-dimethylsilanediyl[2-methyl-4-(3',5'-tert-butylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]dichloride Zirconium, racemic-trans-dimethylsilanediyl[2-methyl-4,8-bis-(4'-tert-butylphenyl)-1,5,6,7-tetrahydro-s-indane-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylindane-1-yl]zirconium dichloride, racemic-trans-dimethylsilanediyl[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indane-1-yl [2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl] zirconium dichloride and rac-trans-dimethylsilanediyl[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3',5'-5-di-tert-butylphenyl)-5-methoxy-6-tert-butylinden-1-yl] zirconium dichloride.
8. The polymer composition according to any one of the preceding claims, characterized in that The β-nucleating agent b) is selected from N,N'-dicyclohexyl-2,6-naphthalene dicarboxamide, quinol[2,3-b]acridine-6,7,13,14(5H,12H)-tetraone, an organic metal salt type β-nucleating agent and a mixture thereof, preferably an organic metal salt type β-nucleating agent, and more preferably the polymer composition does not contain an α-nucleating agent.
9. The polymer composition according to any one of the preceding claims, characterized in that The polymer composition comprises: 99.5 to 99.95 wt. %, preferably 99.6 to 99.8 wt. %, based on the total weight of the polymer composition, of a metallocene-catalyzed heterophasic polypropylene a); and 0.05 to 0.2 wt. %, preferably 0.075 to 0.125 wt. %, based on the total weight of the polymer composition, of a nucleating agent b); wherein: The polymer composition further comprises an additive c) which is different from b), and components a), b) and c) add up to 100% by weight.
10. A film, preferably a blown film, comprising at least one layer comprising at least 90 wt%, preferably at least 95 wt% and more preferably at least 99 wt% of the polymer composition of any one of claims 1 to 9.
11. The film according to claim 10, characterized in that The film comprises a sealing layer comprising the polymer composition of any one of claims 1 to 9.
12. The film according to claim 10 or 11, characterized in that The film has a dart drop strength (ISO 7765-1) of >150 g, preferably in the range of 300 to 1000 g, more preferably in the range of 350 to 600 g.
13. The film according to any one of claims 10 to 12, characterized in that The film has a seal initiation temperature (measured as described in the specification) in the range of 120 to 135°C, preferably in the range of 129 to 131°C.
14. The film according to any one of claims 10 to 13, characterized in that The film has a hot tack in the range of 5.1 to 7.0 N, preferably in the range of 5.3 to 6.0 N (measured as described in the specification).
15. Use of the film according to any of the preceding claims as packaging material, preferably for food and / or pharmaceutical products.
Citation Information
Patent Citations
Polyolefin composition with improved properties
EP1344793A1
Polypropylene film with improved balance of mechanical properties
EP1803772A1
ß-nucleated Propylene Copolymer
EP2055739A1
Polypropylene film having good drawability in a wide temperature range and film properties
US20020137851A1
Thermoformable polypropylene-based sheet
US5310584A